Supervision programs implemented by nurses to caregivers in community: a scoping review protocol - Moreira, Inês; Coelho, Márcia; Mota, Mauro; Pires, Regina; Santos, Margarida Reis (Frontiers in Public Health, 2025)
IntroductionWith the increase in the number of informal caregivers, their training becomes essential. The supervisory programs implemented by nurses play a leading role in caregiver training.ObjectivesTo map the supervisory programs implemented by nurses to caregivers in the community.MethodsA scoping review will be developed according to the guidelines of the Joanna Briggs Institute. Studies published and unpublished in English, Portuguese or Spanish since 1993 will be considered. The results of the research, study selection and inclusion process will be presented in a PRISMA flowchart for scoping reviews.ResultsMapping the evidence will allow us to analyze the supervision programs implemented by nurses for caregivers in the community. The results will be presented through an extraction table according to the objectives.ConclusionThis review is expected to constitute a starting point for the critical analysis of studies relating to supervisory programs implemented by nurses for caregivers.